La socialización frustrada de la industria del Calzado en Barcelona (1936-1939) - Joël Delhom (Cahiers de Civilisation Espagnole Contemporaine)
The socialization of the shoe industry in Barcelona depended on the antifascist trade-unions’ alliance and on the anarcho-syndicalist participation in the government, that reduced its revolutionary significance. The civil war imposed a productivist, centralizing and disciplinary orientation opposed to the emancipatory perspectives, that generated dissatisfaction among the workers and the militants. We focus on the factors that limited the autonomous action of the CNT, the resistances its Agrupación del Calzado had to deal with, the lack of leather and the limitations of the militants in charge. The last part analyses the difficulties of the collectivization from the perception of the grass roots militants.